LVRT Enhancement of a Grid-tied PMSG-based Wind Farm using Static VAR Compensator - Dayo, S. A.; Memon, S. H.; Uqaili, M. A.; Memon, Z. A. (Engineering, Technology & Applied Science Research, 2021)
This paper presents an efficient Low Voltage Ride Through (LVRT) control scheme for a 10.0MW grid-tied Permanent Magnet Synchronous Generator (PMSG)-based wind farm. The proposed control strategy plans to enhance the power quality and amount of injected power to satisfy the grid code requirements. The proposed approach utilizes a static Shunt Var Compensator (SVC) to enhance the LVRT capability and to improve power quality. It has been observed from the outcomes of the study that the proposed SVC controller ensures safe and reliable operation of the considered PMSG-based power system. The proposed system not only improves power quality but also it provides voltage stability of the Wind Energy Conversion System (WECS) under abnormal/fault conditions. The results show the superiority of the proposed control strategy.